ZOONOSES CAUSADAS POR PARASITAS INTESTINAIS DE CÃES E O PROBLEMA DO DIAGNÓSTICO - Katagiri, S. [UNESP]; Oliveira-sequeira, T.c.g. [UNESP] (Instituto Biológico, 2022)
The last 20 years have witnessed a great technological progress along with important cultural and social changes that have improved some aspects of both human and animal health. However, zoonotic diseases caused by dog intestinal parasites persist as a commonplace public health concern in developing countries and as an increasing problem in developed ones. The effectiveness and security of the new drugs available for the prophylaxis and control of parasites has not hindered the emergence of parasitic infection as a serious problem in pets. This review aimed to examine some of the more important intestinal parasites of dogs involved in zoonotic diseases and to highlight issues associated with their diagnosis. The main purpose is to advise veterinarians in clinical practice concerning their importance as a public health agent in preventing and controlling dog zoonotic diseases through the correct use of antiparasite drugs and by educating pet owners.

Os últimos 20 anos foram marcados por um intenso progresso tecnológico e por importantes alterações culturais e sociais com reflexos tanto em saúde humana como animal. Entretanto, infelizmente, as zoonoses causadas por parasitas intestinais de cães não deixaram de ser um problema permanente de saúde pública nos países em desenvolvimento, e uma preocupação crescente nos países desenvolvidos. A eficácia e segurança dos novos produtos disponíveis para a prevenção e controle não impediram que enfermidades parasitárias emergissem como um sério problema em animais de companhia. Nesta revisão, foram consideradas as principais espécies de parasitas intestinais de cães, responsáveis por zoonoses, e os aspectos relativos ao diagnóstico coproparasitológico com o objetivo de contribuir para um maior comprometimento dos médicos veterinários no importante papel de agentes promotores de saúde pública e de difusores do conhecimento.
ZOONOSES CAUSED BY DOG INTESTINAL PARASITES AND THE PROBLEM OF DIAGNOSIS
Keywords: Dogs; intestinal parasites; diagnosis; helminthes; protozoa; Cães; parasitas intestinais; diagnóstico; helmintos; protozoários